Tensile strains in concrete. - Blakey, F. A. (Frank A.) (Report C (CSIRO. Division of Building Research), 1955)
More tensile strain measurements have been made on surface-dry specimens of unreinforced concrete with A.C. electrical resistance strain gauge equipment. The specimens were chosen so that the three conditions of a) equal tension at right angles, b) uniaxial tension, c) equal tension and compression at right angles could be obtained. The results of the measurements agree with those reported in Part I and give further support to the hypothesis of microcrack formation before failure of a concrete specimen. An hypothesis for the criterion of rupture of concrete, which would agree with the results obtained so far, is put forward.